2021
DOI: 10.1101/2021.07.29.454375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cationic motif in Engrailed-2 homeoprotein controls its internalization via selective cell-surface glycosaminoglycans interactions

Abstract: Engrailed-2 (En2) is a transcription factor that possesses as most homeoproteins the unique and intriguing property to transfer from cell to cell through unconventional pathways. The internalization mechanism of this cationic protein is far from being fully understood and is proposed to require an initial interaction with cell-surface glycosaminoglycans (GAGs). To decipher the role of GAGs in the recognition of En2 at the cell surface, we have quantified the internalization of the homeodomain region in cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
1
7
2
Order By: Relevance
“…This RK-OTX2 domain peptide (RKQRRERTTFTRAQL) competes for OTX2 binding to PV cells and antagonizes its specific internalization upon infusion or injection into the cerebral cortex 37 . A similar GAG-binding domain was recently described in EN2 38 and sequence comparisons between OTX2, EN2 and several other HPs identified putative GAG-binding sites in many of them (examples in Figure 7B). In the case of EN1, this domain (RKLKKKKNEKEDKRPRTAF), thereafter RK-EN1, is present between residues 292 and 310 of hEN1.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This RK-OTX2 domain peptide (RKQRRERTTFTRAQL) competes for OTX2 binding to PV cells and antagonizes its specific internalization upon infusion or injection into the cerebral cortex 37 . A similar GAG-binding domain was recently described in EN2 38 and sequence comparisons between OTX2, EN2 and several other HPs identified putative GAG-binding sites in many of them (examples in Figure 7B). In the case of EN1, this domain (RKLKKKKNEKEDKRPRTAF), thereafter RK-EN1, is present between residues 292 and 310 of hEN1.…”
Section: Resultssupporting
confidence: 72%
“…Although we have not directly demonstrated that EN1 binds GAGs, the conservation of the GAG binding domain and the analogy with OTX2 37 and EN2 38 support a specific association of EN1 with MN-expressed GAGs. If this is confirmed by future studies, it will be important to identify the molecular nature of this GAG as done for OTX2, EN2 and also VAX1 9 .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…As an important additional result, it should be underlined that beside the convergent role of GAGs in endocytosis, a few studies also recently highlighted their role in a non-endocytotic internalisation pathway of CPPs, that is through direct translocation at the plasma membrane (Bechara et al ., 2015; Pae et al ., 2016; Takechi-Haraya et al ., 2017; Takechi-Haraya and Saito, 2018). This role of GAGs in the translocation mechanism implies a cross-talk between the peptide, the lipid bilayer and cell-surface GAGs as recently proposed for homeoproteins (Cardon et al ., 2021). In this study, at a temperature at which endocytotic pathways are all inhibited (4 °C), internalisation is reduced in GAG-deficient cells compared to wild-type ones, an observation that clearly supports the role of GAGs in the translocation process.…”
Section: Trp-containing Cpps and Polysaccharidesmentioning
confidence: 99%
“…Interestingly, homeoprotein interaction with GAGs appear to differ between various homeoproteins. Such specificity is illustrated by the binding of OTX2 to highly sulfated chondroitin (CS-E) at the surface of their target cells ( Beurdeley et al, 2012 ), whereas EN2 preferentially interact with heparan sulfate ( Figure 2 ) ( Cardon et al, 2021 ). Interestingly, the presence of cell surface heparan sulfates at the outer leaflet of the plasma membrane is also mandatory for the completion of FGF2 secretion ( Zehe et al, 2006 ).…”
Section: Homeoprotein Secretion and Internalization Two Faces Of A Sa...mentioning
confidence: 99%